
29 Sep
2010
29 Sep
'10
9:19 p.m.
testWhere1 = a where b = 1 a = b+1
testWhere1 2
testWhere2 = a where b = 1 c = 1/(b - b) a = b+1
testWhere2 2.0
The same thing happens with let. testLet1 = let a = b+1 b = 1 in a
testLet1 2
testLet2 = let a = b+1 c = 1/(b - b) b = 1 in a
testLet2 2.0
-- Russ Abbott ______________________________________ Professor, Computer Science California State University, Los Angeles Google voice: 424-242-USA0 (last character is zero) blog: http://russabbott.blogspot.com/ vita: http://sites.google.com/site/russabbott/ ______________________________________